The Perception of Engineers by Middle School Students through Drawings - (:unkn) unknown (ANI YAYINCILIK, 2019)
Purpose: In 2017 and 2018, engineering applications and design process were given weight to with the updates carried out in the Physical Sciences Lesson Curriculum in Turkey. For the STEM education which is at the center of this update to reach its target, it is highly important that students accurately learn what engineers do, what their work field is, the characteristics they should carry and understand the nature of engineering. The present study aims to identify the perception of engineers of 5th, 6th and 7th grade middle school students through drawings. Research Methods: The study group of this research which is a descriptive survey model consisted of 119 students from a city located in the East Anatolian region of Turkey who were 5th, 6th and 7th grade students. The Draw an Engineer form was used as the data collection tool and the drawings were evaluated with a checklist. Findings: As a result of this study, it was determined that a majority of the students adopted the stereotyped idea that engineers are male. The findings showed that as the age increased, the rate of male engineers in the drawings increased as well and engineers creating designs were given more place to. In this study, it was concluded that in general the students mixed up what engineers do with the work construction workers or repairmen do and that they perceived engineers as individuals who work alone. (c) 2019 Ani Publishing Ltd. All rights reserved
Keywords: engineering gender stereotypes; middle school students; STEM education; drawings; EDUCATION